Transforming the Pharmaceutical Supply Chain: The Role of Supply Chain Integration in Connecting Standards Related to Hospital Performance - Quan, Nguyen Huu Khanh; Rajagopal, Premkumar (International Journal of Membrane Science and Technology, 2023)
While integrative care has become standard practice worldwide, a better understanding of the factors driving behaviour, decision-making, collaboration, and governance in care networks is needed to move towards integrative care. The role of supply chain internal and external integration, and its effects on pharmaceutical supply chain performance, has not been studied extensively in the hospital management literature. Supply chain integration adds value to the hospital, demonstrating its efficiency in the pharmaceutical supply chain. This paper proposes a link-oriented model of supply chain integration and performance in the pharmaceutical supply chain. The cross-sectional survey was conducted with 411 pharmacy staff working in Vietnam’s Ho Chi Minh City hospitals. The results indicate that hospital supply chain integration with factors (Human resource management, quality management system, product supply, and information technology) is directly and significantly related to pharmaceutical supply chain performance. The study’s main contribution is the discovery of supply chain integration that links pharmaceutical supply chain performance to disease management paradigm transitions. Theoretical and managerial implications, the scope of future research and the study’s limitations are also discussed.